Efficacy of Reciprocating Instruments in Retreatment of Bioactive and Resin-Based Root Canal Sealers - Danijela Jurić Kaćunić; Antonija Tadin; Petra Dijanić; Adriana Katunarić; Jurica Matijević; Milena Trutina-Gavran; Nada Galić (University of Zagreb. School of Dental Medicine, 2022)
Objective: To compare the effectiveness of reciprocating instruments in removing gutta-percha and bioactive-based (BioRoot RCS and MTA Fillapex) and epoxy resin-based (AH Plus) sealers from root canals based on filling residues and the time required for root canal revision. Material and methods: Root canals of 90 teeth were instrumented with Reciproc R40. All root canals were obturated using the single-cone technique with Reciproc R40 gutta-percha and with one of the selected sealers. Samples with oval, straight canals were used and randomly divided into three groups: (i) filled with AH Plus sealer and gutta-percha (n=30); (ii) filled with MTA Fillapex and gutta-percha (n=30); (iii) filled with BioRoot RCS and gutta-percha (n=30). Each group was divided into two subgroups (n=15) according to the retreatment instrument used (Reciproc M-Wire R25/R40 or Reciproc blue RB25/RB40). Root canals were longitudinally split and analyzed with a stereomicroscope at 15 × magnifications in the coronal, middle, and apical third. Computational analyses were performed with the Image J software. Data were compared using the Kruskal-Wallis test and Mann-Whitney U test. Results: While no statistically significant differences in the residual material surface were found for Reciproc Blue, Reciproc M-Wire showed significantly higher residual material surface for AH Plus and MTA Fillapex compared to BioRoot RCS. For AH plus. Residual material surface was significantly lower for Reciproc Blue than for Reciproc M-Wire. In contrast, BioRoot RCS showed a significantly higher residual material surface for Reciproc Blue. Conclusions: Calcium silicate-containing sealers were more retrievable compared to AH Plus, with fewer sealer remnants and shorter retreatment time. Retreatment with Reciproc M-Wire instruments was superior to Reciproc blue instruments in retreatment of BioRoot RCS. However, none of the sealers were removed completely.